Needs Analysis in Developing PjBL-Based Interactive Media to Improve Student’s Critical Thinking Skills - Asmi, Yuni Karsih; Nisa, Ana Fitrotun; Zulfiani, Heri Maria; Masjid, Akbar Al; Cahyani, Berliana Henu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to provide a description related to the analysis of teacher and student needs in the development of PjBL-based interactive media to improve the critical thinking skills of elementary school students. The research method uses descriptive qualitative research. The results of the teacher needs analysis showed that out of 130 elementary school teachers in the Klaten district, 86.92% of teachers responded that it was necessary to develop interactive media based on project-based learning, and 13.08% of teachers stated that it was not necessary to develop interactive media. Thus, it can be concluded that the development of interactive media based on project-based learning still really needs to be developed. Then, 65 students who were given the question sheet gave answers that 44.62% of students gave answers that teachers only use textbooks in the learning process, 24.62% of students gave answers that they use interactive media in learning, and 75.38% gave responses that students in learning at class do not use interactive media.